Evaluation of the Mexiletine Effects on Normal Cats’ Electrocardiogram - Alireza Narenjian1, Nastaran Rahimi2, Seyed Ali Shabestari Asl1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Mexiletine has been suggested in various studies for the treatment of ventricular arrhythmias. Extremely low toxicity of this drug has been reported in these literatures; however, there is no reasonable report on the effects and function of this drug on the cat’s heart processes in different phases of cardiac contraction. This article evaluated the effects of different dosages of mexiletine on cat’s electrocardiography.Seven cats were used for this study and incremental dosage method with oral capsule has been used. Before starting the study, each cat were evaluated by an electrocardiogram sample, which was considered as a normal electrocardiogram) ECG(. To evaluate the effects of mexiletine, doses of 4, 10, 15, 20 and 40 mg/kg were adjusted and prescribed. For each cat, the doses were prescribed sequentially every 24 hours and after prescription of the drug, the cats were examined clinically and electrocardiographically. This evaluation was done at the peak of the drug, about 2 hours after prescription. Finally, all clinical observations and ECGs were evaluated.In the clinical study, any clinic symptoms was considered and rhythm, heart rate, and determination of heart electrical functions such as P amplitude and duration, QRS duration, R amplitude, ventricular contraction time (QT interval) and PR interval were evaluated in electrocardiographic experiments.According to the results of this study, it can be concluded that the drug is quite safe for cats and no cardiac complication and electrophysiological disorder was observed even with the use of high doses or even incremental doses, so this indicates that the drug can be safe in terms of cardiac effects.